Sarvastivada Buddhist Scholasticism. Charles Willemen, Bart Dessein and Collett Cox. - Gethin, Rupert (Buddhist Studies Review, 2022)
Sarvastivada Buddhist Scholasticism. Charles Willemen, Bart Dessein and Collett Cox. (Handbuch der Orientalistik, HO2, 011), Brill, Leiden 1998. xvii, 341 pp. $109.50. ISBN 90-04-10231-0.